A Comparison of Cost and Complications of Total Ankle Arthroplasty and Ankle Arthrodesis for the Management of Ankle Arthritis: A National Database Study. Issue 3 (14th September 2018) - Tucker, William; Barnds, Bandon; Mullen, Scott; Schroeppel, Paul; Vopat, Bryan
Category: Ankle Arthritis Introduction/Purpose: Ankle arthritis is a relatively common ailment that affects many people. The method of surgical management of this disease process is usually an ankle arthrodesis (AA) or a total ankle replacement (TAR). Traditionally, AA was viewed as the "gold standard", however TAR has grown in popularity. Numerous studies have evaluated the risks and benefits of each of these treatments including satisfaction, biomechanics, and cost. The purpose of this study was to compare the cost and rate of complications for patients who underwent either an AA or TAR using a large database. Methods: Using the PearlDiver Technologies, Inc. database, Medicare patients who were diagnosed with ankle arthritis based on ICD-9 codes from 2005 to 2014 were analyzed. Patients were identified who underwent either AA or TAR utilizing ICD-9 procedure and CPT codes. These patient groups were evaluated for postoperative complications and reoperation rates. Subjects and associated costs were followed after the initial procedure. A cost analysis based on diagnosis and procedural codes was then performed on the separate groups, using a t-test to determine statistical significance. Data was analyzed with regards to standard demographic information as well as a metric of overall patient health status, the Charlson Comorbidity Index (CCI). Results: During the study period, 673, 789 patients were identified with the diagnosis of ankle arthritis. Of those, 19, 120(2.8%) underwent AA and 9, 059 (1.3%) underwent TAR. While the yearly rate of AA performed remained stable, TAR was performed at increasing rates. The overall complication rate in the AA group was 24.9% with a 16.5% revision rate compared to 15.1% and 11.2% respectively in the TAR group (P<0.001). Also, the AA group had a higher total reoperation rate. The CCI was found to be significantly lower in the TAR group at 4.5 versus 4.7 in AA patients (P<0.001). Patients younger than 65 years old had both higher complication and reoperation rate. The average one-year cost associated with TAR was $12, 566.15 and with AA was $6, 967.32 (P<0.001). Conclusion: While TAR was found to be a more expensive treatment option than AA in this large-scale database study, patients in this group had significantly lower complication rates. The reoperation rates were also lower in the TAR group. The CCI was noted to be slightly lower in the arthroplasty group, meaning these patients may have been healthier, representing a selection bias. Also, the patients that had complications were found to have a higher CCI on average. When choosing surgical intervention for end-stage ankle arthritis, patients should be counseled on cost differences and potential complications for TAR and AA.